A Música do Mundo : modos de criação poética em O Barco Vazio, de João Miguel Fernandes Jorge - Cunha, Gualter (1996)
The poems of J. M. Fernandes Jorge in O Barco Vazio are considered as a way of creating meaning from a confrontation of the poet with a devalued world where a few fragmentary things, and the poet's memories of them, still keep their mystery and are therefore worthwhile. Particular attention is paid to the formal processes involved in the organisation of the poems, and to the ethical positioning of the poet expressed in the sometimes not easily attainable unity of the poem. It is argued that the author inherits, and at the same time goes beyond, the modernist tradition.